Diagnostic accuracy of a SARS-CoV-2 rapid antigen test in real-life clinical settings. (August 2021) - Jegerlehner, Sabrina; Suter-Riniker, Franziska; Jent, Philipp; Bittel, Pascal; Nagler, Michael
Highlights: High hopes are placed on SARS-CoV-2 rapid antigen tests Their diagnostic accuracy in clinical settings is essentially unclear A large diagnostic accuracy study was conducted in a real-life clinical setting The diagnostic accuracy of the Roche/SD Biosensor test was 65% Their application might lead to a considerable number of false-negative test results Abstract: Background: Laboratory tests are a mainstay in managing the COVID-19 pandemic, and high hopes are placed on rapid antigen tests. However, the accuracy of rapid antigen tests in real-life clinical settings is unclear because adequately designed diagnostic accuracy studies are essentially lacking. Objectives: The aim of this study was to assess the accuracy of a rapid antigen test in diagnosing SARS-CoV-2 infection in a primary/secondary care testing facility. Methods: Consecutive individuals presenting at a COVID-19 testing facility affiliated to a Swiss University Hospital were recruited ( n  = 1465%). Nasopharyngeal swabs were obtained, and the Roche/SD Biosensor rapid antigen test was conducted in parallel with two real-time PCR tests (reference standard). Results: Among the 1465 patients recruited, RT-PCR was positive in 141 individuals, corresponding to a prevalence of 9.6%. The Roche/SD Biosensor rapid antigen test was positive in 94 patients (6.4%), and negative in 1368 individuals (93.4%; insufficient sample material in 3 patients). The overall sensitivity of the rapid antigen test was 65.3% (95% confidence interval [CI] 56.8–73.1), the specificity was 99.9% (95% CI 99.5–100.0). In asymptomatic individuals, the sensitivity was 44.0% (95% CI 24.4–65.1). Conclusions: The accuracy of the SARS-CoV-2 Roche/SD Biosensor rapid antigen test in diagnosing SARS-CoV-2 infections in a primary/secondary care testing facility was considerably lower compared with the manufacturer's data. Widespread application in such a setting might lead to a considerable number of individuals falsely classified as SARS-CoV-2 negative.